Risk Factors of Neurosensory Disturbance following Orthognathic Surgery - Alolayan, Albraa Badr (Public Library of Science, 2014)
OBJECTIVES: To report the incidence of objective and subjective neurosensory disturbance (NSD) after orthognathic surgery in a major orthognathic centre in Hong Kong, and to investigate the risk factors that contributed to the incidence of NSD after orthognathic surgery. MATERIALS AND METHODS: A retrospective cross-sectional study on NSD after orthognathic surgery in a local major orthognathic centre. Patients who had bimaxillary orthognathic surgery reviewed at post-operative 6 months, 12 months or 24 months were recruited to undergo neurosensory tests with subjective and 3 objective assessments. Possible risk factors of NSD including subjects’ age and gender, surgical procedures and surgeons’ experience were analyzed. RESULTS: 238 patients with 476 sides were recruited. The incidences of subjective NSD after maxillary procedures were 16.2%, 13% and 9.8% at post-operative 6 months, 12 months and 24 months, respectively; the incidences of subjective NSD after mandibular procedures were 35.4%, 36.6% and 34.6% at post-operative 6 months, 12 months and 24 months, respectively. Increased age was found to be a significant risk factor of NSD after orthognathic surgery at short term (at 6 months and 12 months) but not at 24 months. SSO has a significantly higher risk of NSD when compared to VSSO. SSO in combination with anterior mandibular surgery has a higher risk of NSD when compared to VSSO in combination with anterior mandibular surgery or anterior mandibular surgery alone. Gender of patients and surgeons’ experience were not found to be risk factors of NSD after orthognathic surgery. CONCLUSION: The incidence of NSD after maxillary and mandibular orthognathic procedures at post-operative 6 months, 12 months and 24 months was reported. Increased age was identified as a risk factor of short term post-operative NSD but not in long term (24 months or more). Specific mandibular procedures were related to higher incidence of NSD after orthognathic surgery.